Design, Construction and Analysis of Short-Circuited and Probe-Fed Microstrip Based Dipole Arrays - Lim, K.-S.; Tan, C.-P.; Lo, Y.-C.; Leong, W.-S. (VSP BV, BRILL ACADEMIC PUBLISHERS, 2008)
This paper presents the design and development of Short-Circuited Microstrip based Dipole (SCMD) array. The objectives of this array are to achieve wide impedance bandwidth, improve reflection coefficient, S-11 and Voltage Standing Wave Ratio (VSWR). Additionally, a Probe-Fed Microstrip based Dipole (PFMD) array is also constructed to compare the effectiveness of the proposed SCMD array. Both designs are simulated using a three-dimensional electromagnetic simulation tool for design evaluation. In addition, hardware prototypes are also constructed and antenna parameters measurement are conducted in the multipurpose and wideband anechoic chamber in order to verify the actual performance of both designs. Comparison between simulated and measured results for both microstrip based dipole array with different feeding structure of balun is carried out. The proposed SCMD array has shown improved impedance matching, better coupling method and better first side-lobe level suppression compared to PFMD array.